A Guidance Program Based on Behavioural Theory to Reduce Aggressive Behaviour among Kindergarten Children (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to investigate the effectiveness of a counseling program based on behavioral theory in reducing aggressive behavior among preschool children. To achieve this, a quasi-experimental approach was employed. The study sample consisted of 30 children from kindergarten 36, affiliated with Primary School 213 in Jeddah. The participants were randomly divided into two groups: 15 children in the experimental group and 15 in the control group. The Aggressive Behavior Scale for Children, developed by Eman Maher Abdel Fattah (2023), was applied. Using standard statistical methods, the study revealed significant findings, most notably the effectiveness of the counseling program in reducing aggressive behavior. Statistically significant differences were observed at the level of 0.05 between the pre-test and post-test mean scores of the experimental group, favoring the post-test. Additionally, statistically significant differences at the level of 0.05 were found between the post-test mean scores of the experimental and control groups, favoring the experimental group.Based on these findings, it was recommended to conduct training workshops for teachers on utilizing behavioral theory principles to manage aggressive behavior. Furthermore, it was suggested to implement the program regularly and expand its application to various geographical areas and cultural contexts to ensure sustainable positive outcomes. The study also recommended the development of similar programs targeting other behaviors to promote positive behavior among preschool children, particularly after integrating them with early childhood stages.
Keywords: Counseling Program; Behavioral Theory; Aggressive Behavior; Preschool Children